Choroidal thickness in children with type 1 diabetes depending on the pubertal status and metabolic parameters analyzed by optical coherence tomography - Wysocka-Mincewicz Marta (Nature Portfolio, 2021)
Abstract To assess choroidal thickness (CT) in children with type 1diabetes (T1D) regarding their pubertal status and seek for factors influencing this parameter, using optical coherence tomography. Material and methods: 333 eyes out of 167 children with T1D without symptoms of diabetic retinopathy (mean age 12.81 ± 3.63 years, diabetes duration 4.59 ± 3.71 years) were enrolled. CT in all quadrants was evaluated. The studied population was divided into three groups: prepubertal, pubertal and postpubertal. The multivariate regression model was carried out using all metabolic parameter and then it was built using only the significant ones. Results: Significant differences in CT between males and females, except nasal and superior quadrants were observed. We revealed significant differences in CT between the three independent groups (Chi-square 18.6, p < 0.0001). In the statistically significant multiple regression model (R = 0.9, R2 = 0.82, p < 0.0000), the serum level of free thyroxine, triiodothyronine, total hemoglobin, uric acid, low- and high-density cholesterol, daily insulin dose per kilogram, weight and level of vitamin D were significant. Conclusion: In our studied group CT increases during puberty. Metabolic parameters such as cholesterol, uric acid, thyroid hormones, and hemoglobin concentration even within the normal range, significantly influence the CT, and these factors likely affect other blood vessels in the body.